(untitled) (Al-Farooq Journal of Sciences, 2026)
This paper presents a comparative study between the Global Positioning System (GPS) and the Total Station in surveying (topography) work.The research evaluates both devices in terms of accuracy, efficiency, operating conditions, manpower requirements, and suitability for different environments. A practical field experiment was conducted by surveying the same area with both devices, followed by data analysis for coordinate accuracy and time efficiency. The results show that the RTK positioning system provides faster data collection and flexibility in open areas, while the total station provides higher accuracy. Especially in urban environments where line of sight is available, the study concluded that each system has distinct advantages depending on the survey conditions, and a hybrid approach using both devices can achieve optimal results in complex survey projects.